Genetic influence of ABCG2, UGT1A1 and NR1I2 on dolutegravir plasma pharmacokinetics. (3rd February 2020) - Elliot, Emilie R; Neary, Megan; Else, Laura; Khoo, Saye; Moyle, Graeme; Carr, Daniel F; Wang, Xinzhu; Mcclure, Myra; Boffito, Marta; Owen, Andrew
Abstract: Objectives: Dolutegravir has replaced efavirenz as first-line treatment in universal HIV guidelines. We sought to ascertain the contributory effect of SNPs in four key genes linked to dolutegravir disposition ( UGT1A1, ABCG2, CYP3A and NR1I2 ) on plasma dolutegravir pharmacokinetics. Methods: Paired pharmacogenetic/pharmacokinetic data from 93 subjects were analysed for association using multivariate linear regression. Results: Co-occurring UGT1*28 and NR1I2 c.63396C>T homozygosity was associated with a 79% increase in AUC0–24 ( P  =   0.001; 27% if analysed individually), whilst combined ABCG2 c.421C>A and NR1I2 c.63396C>T variants were associated with a 43% increase in C max ( P  =   0.002) and a 39% increase in AUC0–24 ( P  =   0.002). When analysed individually, homozygosity for the NR1I2 c.63396C>T variant alleles was associated with a 28% increase in C max ( P  =   0.033) and homozygosity for the ABCG2 c.421C>A variant alleles was associated with a 28% increase in C max ( P  =   0.047). The UGT1A1*28 (rs8175347) poor metabolizer status (*28/*28; *28/*37; *37/*37) was individually associated with a 27% increase in AUC0–24 ( P  =   0.020). The combination of UGT1A1*28 poor metabolizer and UGT1A1 * 6 intermediate metabolizer statuses correlated with a 43% increase in AUC0–24 ( P  =   0.023). Conclusions: This study showed a pharmacogenetic association between dolutegravir pharmacokinetics and variants in the ABCG2, UGT1A1 and NR1I2 genes, particularly when combined. Further research is warranted to confirm these associations in population-specific studies and to investigate their putative relationship with dolutegravir pharmacodynamics.